Volatility investing with variance swaps - Wolfgang Karl Härdle; Elena Silyakova (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Traditionally volatility is viewed as a measure of variability, or risk, of an underlying asset. However recently investors began to look at volatility from a different angle. It happened due to emergence of a market for new derivative instruments - variance swaps. In this paper first we introduse the general idea of the volatility trading using variance swaps. Then we describe valuation and hedging methodology for vanilla variance swaps as well as for the 3-rd generation volatility derivatives: gamma swaps, corridor variance swaps, conditional variance swaps. Finally we show the results of the performance investigation of one of the most popular volatility strategies - dispersion trading. The strategy was implemented using variance swaps on DAX and its constituents during the 5-years period from 2004 to 2008.
Keywords: C14; G13; 330; Conditional Variance Swap; Corridor Variance Swap; Dispersion Trading; Gamma Swap; Variance Swap; Volatility Replication; Volatility Trading; Swap; Maßzahl; Finanzderivat; Volatilität; Wertpapierhandel; Theorie; Deutschland